Equalizing student and teacher: Using COVID-19 to (re)imagine curriculum - Adams, Megan; Gaines, Rachel; Vasquez, Anete; Noland, Alyssa; Castellano, Faith; Gowdie, Sharae; Carter, Paige (International Journal for Students as Partners, 2023)
COVID-19 created an opportunity to (re)envision students as partners in curriculum development and the curriculum process. Understanding the design and delivery of courses as a flattened hierarchy, particularly with graduate students as partners, is the focus of this study. This article reports findings from research undertaken collaboratively with students as partners in developing a new approach for conducting a capstone course and project. This research was enacted at a research-intensive university in the United States in 2020 and 2021. We describe the need for the shift in stance to students as partners in our institution as well as what the findings indicate as imperatives for teachers in both K–12 settings and institutions of higher education. The findings indicate how teachers’ mental health and experiences of stress were affected by specific attributes of the pandemic and pandemic teaching (which aligns with the majority of COVID-19 research in education), as well as how some learned to cope with these demands. Findings also indicate the need for flexibility in all learning environments.